Points vs. passes: A comparison between electric fishing techniques for sampling fish populations in upland headwater streams - Reagan H. Pearce; Martin R. Perrow; Mark L. Tomlinson; Kirsty A. Turner (Journal of Fish Biology, 2026)
Point‐abundance sampling by electric fishing (PASE) was compared with single‐pass (DF1) and triple‐pass depletion sampling (DF3) electric fishing on the same reaches of four headwater streams sampled over multiple years in the Ribble catchment, UK. Juvenile salmonids, mostly brown trout Salmo trutta with some Atlantic salmon S. salar , or the sculpin, common bullhead Cottus perifretum , dominated the species‐poor fish assemblage in all streams. Generalised linear mixed models and linear mixed models comparing differences in numerical (ind. m −2 ) and biomass density (g m −2 ) found that PASE generally returned statistically significant higher estimates for both measures compared to DF1, with the exception of C. perifretum . In comparison to DF3, PASE tended to underestimate the numerical density of the different species and groups, but the difference was not significant for S. trutta , the dominant salmonid. Moreover, biomass density estimates for all fish combined, combined salmonids and S. trutta were not significantly different. Any differences between PASE and DF3, including for Simpson's Diversity Index and fish median length, were mostly linked to C. perifretum , a small, benthic and cryptic species with low capture probability. Overall, for free‐swimming, commercially important salmonids, PASE performed comparably with DF3 and outperformed DF1. This study suggests that PASE is generally preferable to DF1 and may be a useful alternative to DF3 with the advantages of rapid deployment through reduced sampling effort alongside minimal disturbance and lessened concern over fish welfare. Further comparison of PASE with DF and more research to better verify the effective sampling area of PASE is warranted.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

Live-trapping in the stalk zone of tall grasses as an effective way of monitoring harvest mice (Micromys minutus) - Esther F. Kettel; Martin R. Perrow; Tom Reader (European Journal of Wildlife Research, 2016)

Palaeolimnology as a tool to inform shallow lake management: an example from Upton Great Broad, Norfolk, UK - Kathryn R. Ayres; Carl D. Sayer; Eleanor R. Skeate; Martin R. Perrow (Biodiversity and Conservation, 2008)

Relationships between fish feeding guild and trophic structure in English lowland shallow lakes subject to anthropogenic influence: implications for lake restoration - Luis Zambrano; Martin R. Perrow; Carl D. Sayer; Mark L. Tomlinson; Thomas A. Davidson (Aquatic Ecology, 2006)

Practical application of 25 years' research into the management of shallow lakes - Geoff Phillips; Alison Bramwell; Jo Pitt; Julia Stansfield; Martin Perrow (Hydrobiologia, 1999)

The practical importance of the interactions between fish, zooplankton and macrophytes in shallow lake restoration - Martin R. Perrow; Adrian J.D. Jowitt; Julia H. Stansfield; Geoff L. Phillips (Hydrobiologia, 1999)

Biomanipulation in shallow lakes: state of the art - Martin R. Perrow; Marie-Louise Meijer; Piotr Dawidowicz; Hugo Coops (Hydrobiologia, 1997)

Interactions between piscivores, zooplanktivores and zooplankton in submerged macrophytes: preliminary observations from enclosure and pond experiments - Lene Jacobsen; Martin R. Perrow; Frank Landkildehus; Morten Hjørne; Torben L. Lauridsen; Søren Berg (Hydrobiologia, 1997)

Interactions between coot (Fulica atra) and submerged macrophytes: the role of birds in the restoration process - Martin R. Perrow; J. Hans Schutten; John R. Howes; Tim Holzer; F. Jane Madgwick; Adrian J. D. Jowitt (Hydrobiologia, 1997)

Submerged macrophytes as refuges for grazing Cladocera against fish [-3pt]predation: observations on seasonal changes in relation to macrophyte cover and predation pressure - Julia H. Stansfield; Martin R. Perrow; Louise D. Tench; Adrian J. D. Jowitt; Ayesha A. L. Taylor (Hydrobiologia, 1997)